(untitled) (Revista Apotheke, 2025)
This research investigates artistic processes and materials, exploring techniques for extracting natural dyes and pigments for original productions in painting and installation, presented at the end of the article. The collection of plant and mineral sources dialogues with the artist’s experience in the territory, highlighting his movements and journeys through diverse sources, from the color of the earth, visible in the landscapes, through gardens, vegetable gardens, parks, and markets, to large-scale mining operations. The city—or each place where one lives, whether for a brief period or a lifetime—becomes a studio, a color laboratory, a starting point for the pictorial experience. In chromatic transformations, it is also possible to revisit cultural, historical, and political dimensions, which reveal how the production of paints accompanies social and technological changes over time. In this sense, the use of natural raw materials opens space for the construction of more personal palettes, open to creative deviations, which strengthen autonomy in relation to imported inputs and expand the possibilities for study in contemporary art.